JUDGES PERSPECTIVE ON THE THIRD TALAK IMPOSED OUTSIDE OF COURT SESSION - Nur Rofiq; Meydora Cahya Nugrahenti; Wahyu Prabowo; Ahmad Asroni; Halisma Amili; Taufik Setyaudin; Musthafa Musthafa; Ro’fah Setyowati (Fakultas Hukum, Universitas Diponegoro, 2023)
The research aims to analyze the views of the Panel of Judges, Mediator Judges, Positive Law in Indonesia and Islamic Law regarding triple talak outside the Religious Court hearings. The research method uses the research Normative Law-Empirical and the nature of this research is descriptive-analytic. The results of this research, namely the views of the Panel of Judges, Mediator Judges and Positive Law in Indonesia state that triple talak handed down outside the courtroom is invalid according to Law No. 7 of 1989 concerning Religious Courts and Compilation of Islamic Law Article 117. Meanwhile, according to Law Islam, there are four opinions, namely; First, the one that punishes three divorces imposed at once is three divorces. Second, the opinion condemns that three divorces at the same time only fall one. Third, a detailed opinion, that is a wife who has not had intercourse and has had intercourse with her husband. Three divorces are pronounced simultaneously against a wife who has not had intercourse, then it is divorced one, while divorces against a wife who has been consummated, then it is divorced three. The fourth opinion condemning three divorces at once is not divorced.